Rancang Bangun Safety Device pada Conveyor Menggunakan Arduino Mega - I Putu Genta Maha Permana Wiratmo; Antonius Edy Kristiyono; Ardhiana Puspitacandri (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Unloading equipment is equipment used to assist the process of loading or unloading cargo, such as cargo or bulk cargo from transportation facilities. One example is a conveyor, a mechanical system that can move goods. However, damage often occurs to the conveyor, so an Arduino Mega-based safety device was designed to fulfill the safety aspect. The aim of this research is to find out how to design an Arduino Mega-based safety device system for conveyor unloading equipment using the Research and Development (R&D) method. Using 2 types of testing, namely: static and dynamic testing. Arduino MEGA works fine. If the motor rotates and the conveyor moves, the conveyor is said to be working properly. The safety device on the Arduino Mega-based conveyor was made using Arduino IDE software using the C++ programming language. This safety device is able to secure the conveyor when damage occurs by cutting off the electricity when there is an overload on one of the conveyors so that the entire conveyor stops working. The conveyor series consists of a power supply, box panel, and three conveyors. After the tool has been tested and can work well, the testing is complete and the tool is ready to be used.